Promoting Racial/Ethnic Equity in Psychosocial Treatment Outcomes for Child and Adolescent Anxiety and Depression. Issue 3 (9th September 2022) - Weersing, V. Robin; Gonzalez, Araceli; Hatch, Brigit; Lynch, Frances L.
Abstract : Anxiety and depression are the most prevalent and least treated pediatric mental health problems. Racial/ethnic minority youths face greater risks for developing anxiety and depression and experience higher burden as they are less likely to receive adequate mental health services for these conditions or to have their needs met. Further, standard evidence‐based interventions for youth anxiety and depression may show diminished effects with racial/ethnic minority youths and with families of lower socioeconomic status. While community‐level interventions to combat structural racism and reduce population‐level risk are sorely needed, many youths will continue to require acute treatment services for anxiety and depression and interventionists must understand how to bring equity to the forefront of care. In this review, we adopt a health system framework to examine racial/ethnic disparities in system‐, intervention‐, provider‐, and patient‐level factors for psychosocial treatment of pediatric anxiety and depression. Current evidence on disparities in access and in efficacy of psychosocial intervention for anxious and depressed youths is summarized, and we use our work in primary care as a case example of adapting an intervention to mitigate disparities and increase equity. We conclude with recommendations for disparity action targets at each level of the health system framework and provide example strategies for intervening on these mechanisms to improve the outcomes of racial/ethnic minority youths. Highlights: Racial/ethnic minority youths face greater risks for developing anxiety and depression and experience higher burden from disorder as they are less likely to receive adequate mental health services for these conditions or to have their needs met. Increasing access to services for anxiety and depression is of critical and immediate importance for racial/ethnic minority families. Issues of access may be associated with the physical location of services (e.g., primary care or telehealth) or with barriers of language, income, or financing. Both service settings and research treatment protocols frequently require families of ethnic/racial minority youths to fit themselves to the demands of care, in ways that may not be culturally compatible (e.g., little parent involvement in treatment) or practically feasible (i.e., weekly sessions during parent working hours). Whenever possible, non‐essential aspects of intervention should be freed to match patient preferences and constraints, and interventions for anxiety and depression should be adopted that have broad impacts and options for personalization of goals.